The strategy bridge theory for practice - Gray, Colin S. (Oxford University Press, 2016)
The Strategy Bridge presents the general theory of strategy and explains the utility of this general theory for the particular strategies that strategists need to develop in order to meet their historically unique challenges. The Strategy Bridge regards the strategist as a hero, charged with the feasible, but awesomely difficult, task of converting the threat and use of force (for military strategy) into desired political consequences.